Entre o último suspiro de Lampião, devaneios da estiagem e o Conto do Pé de Feijão: a poética nordestina na animação brasileira - Brandão, Diego Gomes (2013)
This paper aims at analyzying comparatively some aspects of the Mise-en-scène in three contemporaneous national animations focused on the Northesstern theme: "Até o Sol Raiá" (Dir.: Fernando Jorge e Leanndro Amorim, 2007), "Josué e o pé de macaxeira" (Dir.: Diogo Viegas, 2009) and "Three little birds" (Dir.: Lula Buarque e Fábio Soares, 2003). Through the Mass media distribution of Euro-American culture animations disseminated through its cultural industry, we have incorporated technical And stylistic standards saturated By means of production techniques, character design, gags and film editing. The short movies analyzed in this paper show the character of the outlaw and rural workers, Featured in of the contemporary film industry, known as the figure of the Cangaceiro and Countryside folklore, and a Whole poetics expressed through the representation of habits customs, beliefs and artistic-cultural manifestations explored in the visual elements of scenography and costumes. Through an analysis of its formal elements and narrative resources, we seek to understand what meanings are deployed by these animations that somehow not only incorporate into Its creative process the hegemonic paradigms of global animation, but mainly the "season" the social regional context, highlighting our political and social problems, values, emotions, artistic expression and poetic.